2014
DOI: 10.1890/es13-00272.1
|View full text |Cite
|
Sign up to set email alerts
|

Natural recovery of soil organic matter in 30–90‐year‐old abandoned oil and gas wells in sagebrush steppe

Abstract: Abstract. We addressed the rarely studied issue of how different soil organic matter pools respond to disturbances from historical oil and gas well development in semi-arid Intermountain sagebrush steppe. We selected twenty-nine study well sites in south-central Wyoming that were plugged and abandoned 33-90 years ago. We designed our study to understand the long term impact of oil and gas development for soil organic matter pools on non-reclaimed sites, and evaluate the importance of this disturbance type rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 39 publications
0
10
1
1
Order By: Relevance
“…In addition, soil microbial processes can be either accelerated or hampered, often leading to reduction of soil organic matter (Akala andLal 2001, Dangi et al 2012). While changes in bulk density and soil organic matter could explain the slow recovery of big sagebrush species in some cases, our soil analyses suggest that neither bulk density nor organic matter levels were significantly different between disturbed and undisturbed sites (Avirmed et al 2014). We found that big sagebrush density recovered more quickly than big sagebrush cover or biomass.…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…In addition, soil microbial processes can be either accelerated or hampered, often leading to reduction of soil organic matter (Akala andLal 2001, Dangi et al 2012). While changes in bulk density and soil organic matter could explain the slow recovery of big sagebrush species in some cases, our soil analyses suggest that neither bulk density nor organic matter levels were significantly different between disturbed and undisturbed sites (Avirmed et al 2014). We found that big sagebrush density recovered more quickly than big sagebrush cover or biomass.…”
Section: Discussioncontrasting
confidence: 64%
“…Soils in the study area are Typic and Lithic Torriorthents with a mesic and/or frigid temperature regime and an aridic moisture regime (Munn and Arneson 1998). Soil textures in the study area are sandy and sandy loam (Avirmed et al 2014). The study area is characterized by long cool winters and short dry summers and has mean annual temperatures of 5.5-6.08C and mean annual precipitation of 215-343 mm (mean of 1981-2010; PRISM Climate Group 2011).…”
Section: Site Descriptionmentioning
confidence: 99%
“…While this implies that sagebrush has the potential to regenerate following removal, complete recovery of sagebrush vegetation structure clearly requires at least a 3–4 decade time frame (Sturges ; McDaniel, Allen Torell & Ochoa ; Lesica, Cooper & Kudray ; Avirmed et al . ). In addition, enhanced regeneration possibilities following disturbance also underscore the opportunity provided by sagebrush removal for invasive plant species (Anderson & Inouye ), notably exotic annual grasses (Knapp ).…”
Section: Discussionmentioning
confidence: 97%
“…simulated in the reduced biomass grass vegetation (especially at depths > 10 cm) suggest that establishment of sagebrush, and/or other plant species including potential invaders, may be more likely immediately following sagebrush removal. While this implies that sagebrush has the potential to regenerate following removal, complete recovery of sagebrush vegetation structure clearly requires at least a 3-4 decade time frame (Sturges 1993;McDaniel, Allen Torell & Ochoa 2005;Lesica, Cooper & Kudray 2007;Avirmed et al 2014). In addition, enhanced regeneration possibilities following disturbance also underscore the opportunity provided by sagebrush removal for invasive plant species (Anderson & Inouye 2001), notably exotic annual grasses (Knapp 1996).…”
Section: M P L I C a T I O N S F O R S A G E B R U S H E C O S Y S mentioning
confidence: 99%
See 1 more Smart Citation